Phytochemical studies and tlc profile of madhuca longifolia L. Bark with different solvents - K.N. AKSHATHA,; S. MAHADEVA MURTHY,; N. LAKSHMI DEVI, (International Journal of Pharma and Bio Sciences, 2018)
Plants are considered as an alternate source of medicine and are considered as “Drug House” in the future. They have played a significant role in improving the quality of human life and maintaining human health for thousands of years. For a long period of time, plants have been a very good source of herbal products for maintaining human health, especially in the last decade, with more intensive work for natural therapies. The present investigation is mainly focused on the bark of Madhuca longifolia L. tree. Preliminary phytochemical screening with the bark extract using various solvents (Hexane, methanol, water and chloroform) as well as a TLC profile of crude and Liquid-Liquid extraction would be a valuable tool to explore therapeutic approach. Plant derived compounds are playing an important role in the development of several clinically useful medicines with affordable cost.